Nyeri Lutut Berpengaruh terhadap Kemampuan Fungsi Fisik Pasien dengan Osteoarthritis Lutut - Sahrudi Sahrudi; Riri Maria; Tuti Herawati (Poltekkes Kemenkes Jakarta III, 2019)
Osteoarthritis (OA) of the knee can cause a decrease in the ability of physical function that involves movement of the knee joint during the activity. The purpose of this study was to analyze the factors that affect the physical function ability of patients with knee OA. This is a cross sectional study with 96 samples. Bivariate analysis showed gender factor (p = 0,029) and knee pain (p = 0,011) correlated significantly with ability of physical function of knee OA patients, while age factor (P = 0.616), motivation (p = 0.074), body mass index (p = 0.833), knowledge (p = 0.642), and disease comorbidity (p = 0.604) was not related to the physical function ability of knee OA patients. Multivariate analysis showed that knee pain was the most influential factor (dominant) affect the ability of physical function of knee OA patients (p = 0,035; β = 0,217). The furthher research recommendation is to know the characteristics of respondents who are more heterogeneous to the ability of physical function.